Consequences of pandemic-associated social restrictions: Role of social support and the oxytocin system. (January 2022) - Gryksa, Katharina; Neumann, Inga D.
Abstract: During pandemics, governments take drastic actions to prevent the spreading of the disease, as seen during the present COVID-19 crisis. Sanctions of lockdown, social distancing and quarantine urge people to exclusively work and teach at home and to restrict social contacts to a minimum; lonely people get into further isolation, while families` nerves are strained to the extreme. Overall, this results in a dramatic and chronic increase in the level of psychosocial stress over several months mainly caused by i) social isolation and ii) psychosocial stress associated with overcrowding, social tension in families, and domestic violence. Moreover, pandemic-associated social restrictions are accompanied by loss of an essential stress buffer and important parameter for general mental and physical health: social support. Chronic psychosocial stress and, in particular, social isolation and lack of social support affect not only mental health, but also the brain oxytocin system and the immune system. Hence, pandemic-associated social restrictions are expected to increase the risk of developing psychopathologies, such as depression, anxiety-related and posttraumatic stress disorders, on the one hand, but also to induce a general inflammatory state and to impair the course of infectious disorders on the other. Due to its pro-social and stress-buffering effects, resulting in an anti-inflammatory state in case of disease, the role of the neuropeptide oxytocin will be discussed and critically considered as an emerging treatment option in cases of pandemic-induced psychosocial stress, viral infection and during recovery. In this review, we aim to critically focus on possible short- and long-term consequences of social restrictions on mental health and the immune system, while discussion oxytocin as a possible treatment option. Highlights: Pandemic-induced social restrictions cause social isolation on the one side and social tension in families on the other. This results in increased stress susceptibility, and impaired mental and general health. Lack of the stress buffering effect of social support further impairs both the immune system and mental health. Due to its multiple beneficial effects, the neuropeptide oxytocin is critically discussed as an emerging treatment option.